Soil carbon persistence governed by plant input and mineral protection at regional and global scales - Chen, Leiyi; Fang, Kai; Wei, Bin; Qin, Shuqi; Feng, Xuehui; Hu, Tianyu; Ji, Chengjun; Yang, Yuanhe; Cleland, Elsa (Ecology letters, 2021)
Elucidating the processes underlying the persistence of soil organic matter (SOM) is a prerequisite for projecting soil carbon feedback to climate change. However, the potential role of plant carbon input in regulating the multi‐layer SOM preservation over broad geographic scales remains unclear. Based on large‐scale soil radiocarbon (∆14C) measurements on the Tibetan Plateau, we found that plant carbon input was the major contributor to topsoil carbon destabilisation despite the significant associations of topsoil ∆14C with climatic and mineral variables as well as SOM chemical composition. By contrast, mineral protection by iron–aluminium oxides and cations became more important in preserving SOM in deep soils. These regional observations were confirmed by a global synthesis derived from the International Soil Radiocarbon Database (ISRaD). Our findings illustrate different effects of plant carbon input on SOM persistence across soil layers, providing new insights for models to better predict multi‐layer soil carbon dynamics under changing environments. Elucidating the processes underlying the persistence of soil organic matter (SOM) is a prerequisite for accurately projecting soil carbon feedback to climate change. Based on large‐scale soil radiocarbon (∆14C) measurements from the Tibetan Plateau and International Soil Radiocarbon Database (ISRaD), we found that the predominant factors that regulate soil ∆14C were depth dependent: plant carbon input was the major contributor to topsoil carbon destabilization, whereas mineral protection became more important in modulating ∆14C in the subsoil.